Bilateral choanal atresia - Luh Putu Lusy Indrawati; Muhammad Syafiq Riski; Ranita Parjaman (Oto Rhino Laryngologica Indonesiana, 2021)
ABSTRACTBackground: Choanal atresia is an uncommon anomaly that causes upper airway obstruction in newborns, with a frequency of 1 in 5000 to 7000 births. The definitive treatment is surgery. Purpose: To inform the diagnosis and management of a bilateral choanal atresia. Case report: A 2-months-old girl with a diagnosis of bilateral choanal atresia. The patient underwent transnasal endoscopic repair of choanal atresia under general anesthesia. Clinical question: Could transnasal endoscopic repair of choanal atresia followed by stenting, provide better result than other approaches? Review method: Literature search using keywords ’choanal atresia’ AND ’bilateral’ AND ’membranous’ AND ’endoscopic’ AND ’surgery’ AND ’stent’ was conducted through PubMed, Science Direct, and The Cochrane Library. Result: The search obtained 34 articles concerning choanal atresia. Selection based on inclusion and exclusion criteria, found 15 articles were relevant with the topic. Conclusion: A baby girl came with bilateral choanal atresia. The diagnosis was established by nasoendoscopy, supported by CT imaging. She underwent transnasal endoscopic repair of the stenotic choanae under general anesthesia.Keywords: bilateral choanal atresia, transnasal endoscopic surgery, congenital nasal airway anomalyABSTRAKLatar belakang: Atresia koana merupakan kelainan pada neonatus yang jarang terjadi, yang dapat menyebabkan obstruksi jalan napas atas. Frekuensi kasus sebanyak 1 dari 5000 sampai 7000 kelahiran. Tatalaksana definitif pada kasus atresia koana adalah tindakan operatif. Tujuan: Memberikan informasi mengenai diagnosis dan tatalaksana atresia koana bilateral. Laporan kasus: Bayi berusia 2 bulan dengan diagnosis atresia koana bilateral. Tatalaksana pada kasus ini adalah operasi membuka koana dengan pendekatan endoskopi transnasal. Pertanyaan klinis: Apakah tatalaksana operasi perbaikan atresia koana dengan pendekatan transnasal endoskopi yang diikuti dengan pemasangan stent lebih baik dibandingkan dengan pendekatan lain? Telaah literatur: Dilakukan penelusuran menggunakan kata kunci ’choanal atresia’ DAN ’bilateral’ DAN ’membranous’ DAN ’endoscopic’ DAN ’surgery’ DAN ’stent’ pada beberapa sumber data seperti PubMed, Science Direct, dan The Cochrane Library. Hasil: Didapatkan 34 artikel yang membahas atresia koana. Melalui kriteria inklusi dan eksklusi diperoleh 15 artikel yang relevan dengan topik. Kesimpulan: Telah dilaporkan pasien dengan diagnosis atresia koana bilateral. Diagnosis ditegakkan melalui endoskopi transnasal dan CT scan. Dilakukan perbaikan koana menggunakan pendekatan endoskopi transnasal, dengan anestesi umum.Kata kunci: atresia koana bilateral, endoskopi transnasal, kelainan kongenital hidung